video Art of “Bannan0gsata Case Study”: Women Muteness - Phuyuthanon, I-na (Institut Seni Indonesia Yogyakarta, 2018)
Video art is conveyance of creation of human emotions from a person who share similar emotions using digital media. It is conveyed through spiritual and emotional movements of the creators with definite aims concerning traditions, customs, beliefs, religions, and local ways of life. A range of issues in three border provinces of southern Thailand: Yala, Pattani, and Narathiwat, were brought up. With depiction of separatist terrorism in the area, video art might be able to tell complicated, over-a-decade-long story triggered by two incidents: the Tak Bai Incident and the clash at Krue Sae Mosque, which brought the three provinces to public attention. The video art provides a way to understand the society, human empathy, and conflict of interest in Bannangsata District. These aspects were conveyed through the local’s ways of life with religion as a spiritual keeping by believing that God has determined everything and that they, as human, have to face any test they are given. The end of the video art presented what cannot be narrated by words about the area, and showed more than what the news may offer, which intensifies fear.The researcher studied various aspects of Bannangsata District and has shown them through a type of artistic media called video art, specifically about the issue of women’s suppression as experienced by those who survived series of tragic incidents. The video art aimed to raise awareness about changes of a way of life in the area and to create sympathy for fellow human beings there. The researcher realized that empathy for fellow human beings was significant for the existence of the world and that it cannot be relinquished. Thus, this art media was made to portray the issue of complicated troubles in the area.